2022
DOI: 10.24193/adn.15.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subject jigsaw and reading writing presentation techniques on academic achievement of 7th grade science students’ academic success in structure and properties of matter

Abstract: "In this article a recently developed method, Reading Writing and Presentation (RWP) was introduced and compared with Subject Jigsaw Method (JG) and Control Group (CG). CG studied with present curriculum which was designed with respect to constructivism and issued by National Ministry of Education. Research was carried out with 7th grade elementary school students. Number of students included in RWP group was 22, in JG were 27 and in CG were 20. Thus, total number of the students enrolled in the study was 69. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…al. 2021;Akkus and Doymus, 2022;Krakas, 2022). Even though policy documents emphasize that text books and LTSM play an important role in improving learning outcomes (UNESCO 2016), researchers indicated that the use of LTSM sometime has a limited impact on learners (Milligan et.…”
Section: Factors Behind Quality School Educationmentioning
confidence: 99%
“…al. 2021;Akkus and Doymus, 2022;Krakas, 2022). Even though policy documents emphasize that text books and LTSM play an important role in improving learning outcomes (UNESCO 2016), researchers indicated that the use of LTSM sometime has a limited impact on learners (Milligan et.…”
Section: Factors Behind Quality School Educationmentioning
confidence: 99%